(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
When treating victims with TBM accompanied by traumatic intracranial hemorrhage, one should also take into account factors of secondary brain damage, which are not directly related to the mechanism of its primary damage, but always affect the course of the post-traumatic period and the prognosis of outcome. Prevention of complications largely depends on understanding the mechanisms and nature of brain damage (1,2,3).